Future developments in sociology in the age of the metaverse - Auriemma, Vincenzo (Frontiers in Sociology, 2023)
The intent of this article is to shed light on the future challenges that sociology, in concert with other disciplines, will have to face from now on, starting with one of the possible hypotheses of research methodology. Indeed, as much as some of these issues in the last two decades have become the preserve of neuroscience, their origins, namely the conceptualizations of the classics of sociology, should not be forgotten. In this regard, it will be the task of researchers and sociology to investigate, through applied research attempts, phenomena such as empathy and emotions from innovative methodologies and research different from the current ones, capable of highlighting how emotions are modified by cultural context and spaces of interaction, moving away from a depersonalizing structuralism we were used to, refuting, for example, what neuroscientists have pointed out, according to which empathy and emotions belong to biological universalisms. Therefore, within this brief and informative article we intend to present a possibility of investigation, without any claim to truth or the only way to be able to do research in this field, moved only by the desire to open a fruitful discourse that can lead to the methodological approach toward applied sociology or laboratory research. The idea is to move beyond online netnography, not because the latter cannot provide satisfactory results, but because it will be necessary to broaden the range of choices, such as analysis in the metaverse, generating a viable alternative where this type of analysis cannot be pursued.